2019
DOI: 10.1063/1.5086491
|View full text |Cite
|
Sign up to set email alerts
|

A fast and accurate piezoelectric actuator modeling method based on truncated least squares support vector regression

Abstract: In order to improve the applicability of piezoelectric actuators (PEAs) in precision positioning, least squares support vector regression (LS-SVR) is applied to model hysteresis in PEAs due to its high modeling accuracy and fast convergence speed. However, low robustness of LS-SVR makes modeling accuracy susceptible to noises, which makes LS-SVR hysteresis models difficult to be applied in engineering environment. In this article, a robust truncated least squares support vector regression (T-LSSVR) is proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…To overcome the overfitting problem, the authors in [ 26 , 27 , 28 , 29 ] proposed hysteresis models based on a regression algorithm. The input of the hysteresis model was selected based on an autoregressive model with exogenous input (NARX), where the current output is dependent not only on the current inputs but also on the past inputs and past outputs.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the overfitting problem, the authors in [ 26 , 27 , 28 , 29 ] proposed hysteresis models based on a regression algorithm. The input of the hysteresis model was selected based on an autoregressive model with exogenous input (NARX), where the current output is dependent not only on the current inputs but also on the past inputs and past outputs.…”
Section: Introductionmentioning
confidence: 99%
“…As LSSVM only deals with one-to-one mapping, whereas hysteresis is defined as multi-valued, few studies have attempted to provide a suitable hysteresis map, often based on expanding input space into multidimensional space. For instance, the authors in [19][20][21][22] used nonlinear autoregressive exogenous (NARX) models in which the input was expanded to include current and past inputs, as well as the past outputs. Although the results showed that the outputs could be well-predicted, the output of the inverse LSSVM-NARX model that is fed to its input usually results in accumulated errors over time [23,24].…”
Section: Introductionmentioning
confidence: 99%